PENGGUNAAN MODEL PEMBELAJARAN POGIL (PROCESS ORIENTED GUIDED INQUIRY LEARNING) TERHADAP HASIL BELAJAR SEKOLAH DASAR - Silvia Yoki Handayani; Iis Aprinawati; Yanti Yandri Kusuma; Muffarizudin Muffarizudin; Rizki Ananda (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2022)
This research is motivated by the low learning outcomes of students at school base. One of the efforts to overcome this problem is to using the POGIL learning model (Process Oriented Guided Inquiry Learning). In this study, Quantitative. The research design used by the researcher is “Nonequivalent control group design” or quasi-experimental research. Study This was done at SDN 020 Ridan Permai. Cempaka Putih Street, Bangkinang City, in Class VB-VC Semester 2 (Even) with a total of 23 students in VB class and VCclass. Dataccollection techniquesmused inmresearch This is an interview and test questions (pre-test and post-test) Oriented Guided Inquiry Learning) is higher than the learning outcomes using the conventional. This can be seen from the T test with a significant level of 0.001 < 0.05 then HO is rejected and Ha is accepted. So it can be concluded that there is a difference which is significant in science learning outcomes between POGIL. learning models (Process Oriented Guided Learning) in class VB